Intraflagellar transport complex structure and cargo interactions - Bhogaraju, Sagar (BioMed Central, 2013)
Intraflagellar transport (IFT) is required for the assembly and maintenance of cilia, as well as the proper function of ciliary motility and signaling. IFT is powered by molecular motors that move along the axonemal microtubules, carrying large complexes of IFT proteins that travel together as so-called trains. IFT complexes likely function as adaptors that mediate interactions between anterograde/retrograde motors and ciliary cargoes, facilitating cargo transport between the base and tip of the cilium. Here, we provide an up-to-date review of IFT complex structure and architecture, and discuss how interactions with cargoes and motors may be achieved.